2015
DOI: 10.1530/joe-14-0662
|View full text |Cite
|
Sign up to set email alerts
|

The role of Nrf2 in oxidative stress-induced endothelial injuries

Abstract: Endothelial dysfunction is an important risk factor for cardiovascular disease, and it represents the initial step in the pathogenesis of atherosclerosis. Failure to protect against oxidative stress-induced cellular damage accounts for endothelial dysfunction in the majority of pathophysiological conditions. Numerous antioxidant pathways are involved in cellular redox homeostasis, among which the nuclear factor-E2-related factor 2 (Nrf2)/Kelch-like ECH-associated protein 1 (Keap1)-antioxidant response element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
249
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(265 citation statements)
references
References 132 publications
(102 reference statements)
12
249
0
4
Order By: Relevance
“…Nrf2 is currently considered a key transcription factor that regulates the defense of cells against oxidative injury [39][40][41][42]. Upon exposure to ROS or the indirect effect of phosphorylation, Nrf2 is released from Keap1 and translocated into the nucleus to bind to the ARE sequence, triggering the transcription of downstream phase II antioxidant genes, such as catalase (CAT), NADPH: quinone oxidoreductase (NQO1), superoxide dismutase (SOD), thioredoxin 1 (Trx-1), and heme oxygenase-1 (HO-1), and enhancing the antioxidant capacity of cells [12,13,43,44]. Present studies suggested that PI3K and MAPK pathways are signal transduction pathways mainly involved in the activation of Nrf2/ARE and its downstream phase II detoxification enzyme, as well as the gene expression of antioxidant enzymes [14,45].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is currently considered a key transcription factor that regulates the defense of cells against oxidative injury [39][40][41][42]. Upon exposure to ROS or the indirect effect of phosphorylation, Nrf2 is released from Keap1 and translocated into the nucleus to bind to the ARE sequence, triggering the transcription of downstream phase II antioxidant genes, such as catalase (CAT), NADPH: quinone oxidoreductase (NQO1), superoxide dismutase (SOD), thioredoxin 1 (Trx-1), and heme oxygenase-1 (HO-1), and enhancing the antioxidant capacity of cells [12,13,43,44]. Present studies suggested that PI3K and MAPK pathways are signal transduction pathways mainly involved in the activation of Nrf2/ARE and its downstream phase II detoxification enzyme, as well as the gene expression of antioxidant enzymes [14,45].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a protein that regulates the body's antioxidant response to oxidative stress 67,68 . Nrf2 has been called the 'thermostat' within our cells because it can determine the level of oxidative stress and initiate an antioxidant protective response to combat the stress 67,68 .…”
Section: Nrf2 Activation Is the Future Of Cellular Protectionmentioning
confidence: 99%
“…Nrf2 has been called the 'thermostat' within our cells because it can determine the level of oxidative stress and initiate an antioxidant protective response to combat the stress 67,68 . Nrf2 activation enables our cells to use their own antioxidant reserve from naturally-occurring and plant-derived activators, such as sulforaphane from broccoli and curcumin from turmeric 67,68 . Some Nrf2 activators are synthetic compounds and thus must be developed by pharmaceutical treatments 67,68 .…”
Section: Nrf2 Activation Is the Future Of Cellular Protectionmentioning
confidence: 99%
See 2 more Smart Citations